Youth tourism in South Africa: the case of language travel - Correia, Maisa (My University, 2011)
Language travel has become a growing industry under the youth travel umbrella. Key destination countries such as Australia, USA and the UK have recognised this industry as a significant contributor to their tourism economy. Despite these initiatives to actively develop language tourism as a major incoming market, little attention has been paid to language travel in research, especially in South Africa. It is shown that language schools are unevenly distributed across the country. In South Africa, the Western Cape (Cape Town in particular) dominates the local language travel industry, followed by Gauteng. The study analyses the organisation and development of the language travel industry in South Africa as part of the country’s youth tourism economy. It is shown that considerable differences exist between coastal language schools and inland schools. Although both operate in the same industry there are marked differences in operation and source markets for students. This report explores South Africa’s language travel industry in terms of its position in the global language travel industry, its development, size, key role players, structure, operation, and significance for the greater South African tourism economy